Emotion recognition and alexithymia in high functioning females with autism spectrum disorder. (January 2016) - Ketelaars, Mieke P.; In't Velt, Anne; Mol, Audrey; Swaab, Hanna; van Rijn, Sophie
Highlights: The phenotype of women with ASD is distinct from that of men. Women with ASD exhibit normal visual and vocal emotion recognition skills. Women with ASD show high levels of alexithymia. Alexithymia is related to difficulties recognizing visual emotions of low intensity. Abstract: Although there is a wealth of information on the emotion recognition skills of males with autism spectrum disorders (ASD), not much is known about these skills in women with ASD. This study investigates the relation between alexithymia and emotion recognition in this group. 31 high-functioning females with ASD and 28 age matched typical females performed a vocal and visual emotion recognition task and completed an alexithymia questionnaire. Level of intensity of the presented emotions was manipulated in the visual emotion recognition task between 25% (low intensity) and 100% (full emotion intensity) in 25% increments. There was no evidence of impairments in the accuracy of visual or vocal emotion recognition. Both groups were equally affected by level of intensity. Level of alexithymia was higher in women with ASD in the cognitive domain. Within the ASD group, women with high levels of alexithymia attained lower scores on visual emotion recognition in the lowest intensity condition, suggesting that being able to identify one's own emotions may help in processing subtle emotions.